2015
DOI: 10.1051/0004-6361/201425304
|View full text |Cite
|
Sign up to set email alerts
|

Short-term variability on the surface of (1) Ceres

Abstract: Context. The dwarf planet (1) Ceres -next target of the NASA Dawn mission -is the largest body in the asteroid main belt. Although several observations of this body have been performed so far, the presence of surface water ice is still questioned. Aims. Our goal is to better understand the surface composition of Ceres and to constrain the presence of exposed water ice. Methods. We acquired new visible and near-infrared spectra at the Telescopio Nazionale Galileo (La Palma, Spain), and reanalyzed literature spe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 31 publications
2
18
2
Order By: Relevance
“…Table 1 reports the observational circumstances. We used the ESO-MIDAS software package and standard procedures to reduce the obtained data (see Perna et al 2015 for details). The wavelength calibration of DOLORES data was performed using Ar, Ne+Hg, and Kr lamps' spectral lines, while NIR spectra were calibrated through a look-up table available at the NICS website.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…Table 1 reports the observational circumstances. We used the ESO-MIDAS software package and standard procedures to reduce the obtained data (see Perna et al 2015 for details). The wavelength calibration of DOLORES data was performed using Ar, Ne+Hg, and Kr lamps' spectral lines, while NIR spectra were calibrated through a look-up table available at the NICS website.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…Data were reduced using standard procedures (bias and background subtraction, flat field correction, one-dimensional spectra extraction, atmospheric extinction correction-see Perna et al 2015 for more details). Wavelength calibration was generally obtained using emission lines from several lamps.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…Therefore, if the outgassing on Ceres were triggered by sporadic impact events similar to that considered for Scheila, then such events would not directly produce albedo changes with ejecta near the impact site detectable here. Perna et al (2015) suggested that Ceres displays short-term (months) visible spectral variability, and attributed it to "extended resurfacing processes such as cryovolcanism or cometary activity." Our interpretation of the ground-based visible wavelength spectral data shows an increasing spectral slope with increasing phase angle (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Bright spots within impact craters Dantu (125 km) and Occator (92 km) have been linked to intermittent and localized water vapor sources observed by the Herschel Space Observatory in 2011-2013 (Küppers et al 2014), and are, therefore, possibly related to the sublimation activity. Recent ground-based observations of Ceres also suggested short-term global spectral variability that was attributed to the changing amount of water ice on the surface (Perna et al 2015). These observations suggest a possibly changing surface caused by water outgassing on timescales of decades to months.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation